DIGITALISASI SEBAGAI PENGEMBANGAN PENGELOLAAN PASAR TRADISIONAL (STUDI KASUS : PASAR DEPOK KOTA SURAKARTA) - Surasno, Aberona Thea Chenarani; Prasetyani, Dwi; Samudro, Bhimo Rizky (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Along with the times, traditional markets need innovation to survive. traditional markets need to adapt not only to modern markets but also to the rise of online markets or e-commerce. Digitalization as a way of developing Depok Market is interesting to study. This paper aims to determine the market development strategy in the era of digitalization and implementation challenges of digitization in the traditional market. This study uses a qualitative method with descriptive analysis. The research data were collected by field observations, interviews, and document review methods (content analysis). The results showed that the strategy used for the development of the Depok Market was to implement e-retribution and encourage non-cash transactions. The challenges faced in its implementation are the e-retribution machine facilities which often have errors and the ability of traders to carry out non-cash transactions is not evenly distributed.